EFEKTIVITAS IZIN GANGGUAN DAN PROBLEMATIKA HUKUMNYA SETELAH PERMENDAGRI 19/2017 - Bastian, Jimmy; Michael, Tomy (Institut Hindu Dharma Negeri Denpasar, 2018)
Any person or entity that wishes to carry out a particular activity which may cause harm, harm, and disruption shall equip themselves with a Disturbance License or Hinder Ordonnantie. The granting of the Nuisance License in general is the authority of the bupati or mayor. In carrying out Nuisance Licenses, the Regional Government may impose a levy called the Distribution License License. The existence of this levy is considered very useful for the Region because it provides a substantial income for the local treasury. However, in early 2017, the Minister of Home Affairs Tjahjo Kumolo revoked the Regulation of the Minister of Home Affairs which regulated the guidelines for the determination of permit disruption in the region. That way, all local regulations governing Nuisance Permissions automatically no longer have a legal basis. So that local government since that time practically no longer able to organize Nuisance Permit. In fact, the authority of the Region to administer the permit is an authority born by Hinder Ordonnantie which is a legally binding regulation of wetgevende organization in colonial Indonesia. Legal research conducted with historical approaches and legislation is intended to describe the authority of the Region in organizing Nuisance Permits.